Decay estimates for Timoshenko systems with complementary frictional damping and memory effect. (October 2020) - Zhang, Hui
Abstract: We consider the decay rate of Timoshenko type equations for beams with complementary frictional damping and memory effect in an interval. Under only basic conditions on the memory kernels (without any decaying conditions), we show that the solution energy of Timoshenko systems decays uniformly at the rate t − 1 . Simultaneously, the same rate is also obtained for the corresponding single memory-dissipative wave equation. The proof is based on some appropriate functionals and it improves the previously related results in the literature.